The Egyptian Miracles of Saints Cosmas and Damian in the London Codex (Rupprecht, Lond. Add. 37534 = BHG 373b) - Csepregi, Ildikó; Movrin, David (Classica et Mediaevalia, 2025)
Patron saints of doctors, surgeons and pharmacists, Saint Cosmas and Damian were among the most popular and important figures of Byzantine hagiography. They healed through incubation, temple sleep, by giving miraculously medical recipies or performed surgical operations in dreams. Their cult was popular and their worship is attested all over the Mediterraneum. The present text is the first modern translation of the oldest version of their miracles, from a 10th or 11th-century Greek codex found in Egypt, now in the British Library (Cod. Lond. Add. 37534). Its simple and unadorned style offers a rich material for examining the emergence of Byzantine hagiography, a precious source of comparison with the better-known, later miracles of Cosmas and Damian and the theological controversies of the time.